Macrobenthic Mollusca of the Prince Gustav Channel, Eastern Antarctic Peninsula: An Area Undergoing Colonisation - Anderson, Madeline P. B. C.; Fenberg, Phillip B.; Griffiths, Huw J.; Linse, Katrin (Frontiers in Marine Science, 2021)
In 2018 RRS James Clark Ross investigated the marine benthic biodiversity of the Prince Gustav Channel area which separates the eastern coast of the Antarctic Peninsula from James Ross Island. The southern end of this channel had been covered by the Prince Gustav Ice Shelf until its collapse in 1995. Benthic samples were collected by an epibenthic sledge at six stations (200–1,200 m depth) in the channel and adjacent Duse Bay. In total 20,307 live collected mollusc specimens belonging to 50 species and 4 classes (Solenogastres, Bivalvia, Gastropoda, and Scaphopoda) were identified. The area may be characterised by it’s low species richness (ranging from 7 to 39 species per station) but high abundances (specifically of the Scaphopods with 11,331 specimens). The functional traits of the community were dominated by motile development and mobility type. Assemblage analyses of the molluscan species abundances within the Prince Gustav Channel stations sit distinct, with no pattern by depth or location. However, when bivalve assemblages were analysed with reference to the wider Weddell Gyre region (15 stations from 300 to 2,000 m depth), the Prince Gustav Channel sits distinct from the other Weddell Gyre stations with a higher dissimilarity between the deeper or more geographically distant areas. The Prince Gustav Channel is undergoing colonisation following the recent ice shelf collapse. With many Antarctic ice shelves threatened under climate warming, this area, with future monitoring, may serve as a case study of benthic faunal succession.